An improved glucose transport assay system for isolated mouse skeletal muscle tissues. Issue 11 (1st November 2016) - Inagaki, Akiko; Maruo, Kanoko; Furuichi, Yasuro; Miyatake, Shouta; Tamura, Kotaro; Fujii, Nobuharu L.; Manabe, Yasuko
Abstract : There is a growing demand for a system in the field of sarcopenia and diabetes research that could be used to evaluate the effects of functional food ingredients that enhance muscle mass/contractile force or muscle glucose uptake. In this study, we developed a new type of in vitro muscle incubation system that systemizes an apparatus for muscle incubation, using an electrode, a transducer, an incubator, and a pulse generator in a compact design. The new system enables us to analyze the muscle force stimulated by the electric pulses and glucose uptake during contraction and it may thus be a useful tool for analyzing the metabolic changes that occur during muscle contraction. The system may also contribute to the assessments of new food ingredients that act directly on skeletal muscle in the treatment of sarcopenia and diabetes. Graphical abstract: Development of the new in vivo skeletal muscle contraction systems.